Starlight An Introduction to Stellar Physics for Amateurs - Robinson, Keith (The Patrick Moore Practical Astronomy Series, 2009)
When you look up at the sky at night and see the stars, do you understand what you're looking at? What is starlight made up of, and how does it travel to us? How are stars born, and how do they die? How do we figure out how far away are the stars and how massive they are? Can we know which stars will go supernova and which will end up as white dwarfs or black holes? How long will our Sun continue to shine down on us, and how do we know its age? There are so many questions, and in this engaging and informative book by Keith Robinson, which serves as a companion to his very popular earlier book called Spectroscopy - the Key to the Stars, you will learn the basics of stellar physics and the answers to many of these questions, as well as how to figure out some of those answers for yourself. We have come so far in our understanding of stellar light and heat. By reading this book, you, too, can understand many of the secrets of the fiery Sun that rules our Solar System and the gemlike points of light in the night sky.